Assistance in the Use of a Website-Based Disability Sports Competition Management System for NPCI Coaches and Officials throughout East Java - Dwi Cahyo Kartiko; Irmantara Subagio; Bayu Budi Prakoso; Suryanto Agung Prabowo; Rudi Rudi; Roy Agustinus Soselisa (Abdi Masyarakat, 2026)
National Paralympic Committee Indonesia (NPCI) East Java manages disability sports competitions across East Java Province. However, competition management faces three major challenges: (1) the absence of technology-based competition management systems; (2) limited understanding of disability classification among coaches and officials leading to frequent misplacement of athletes; and (3) infrequent competency enhancement activities for district/city NPCI coaches and officials. This community service (PkM) activity aimed to accompany coaches and officials from NPCI across East Java in using a website-based competition management system, implemented directly during the East Java Provincial Paralympic Championship (Peparprov II) 2024, June 13–17, 2024, at the Oentoeng Poedjadi Athletics Track, FIKK Universitas Negeri Surabaya. A total of 92 coaches and officials from 29 districts/cities participated actively. Evaluation of training quality using a 19-item instrument across four aspects showed an overall average of 4.49 (89.9%), categorized as very good, with presenter competence receiving the highest score (4.51; 90.3%). Website usability evaluation using 19 items across four dimensions showed an overall average of 4.12 (82.5%), categorized as good, with ease of use and content dimensions receiving the highest scores (4.15; 83.0%). Outcomes achieved include improved competencies of coaches and officials, successful implementation of the website system during Peparprov II, mass media publication, and a formal cooperation agreement between FIKK Unesa and NPCI East Java.